The Provisions Related to the Nursery of the Non -Muslim Are a Jurisprudential Study - Ahmed, Abdulkhalek Mohamed (Dirasat: Shari’a and Law Sciences, 2024)
Objectives: This research aims to clarify the rulings on the custody of children in the event of difference in religion between the custodian and the ward who comes forward in the event of a Muslim meeting with a non-Muslim, and the residence and maintenance of children. The importance of this research is due to its handling of an important and influential topic as it relates to the custody of children in the event of a difference in religion.. Methods: The study adopted the inductive, analytical, and descriptive methods by presenting the views of the scholars from the recognized legal schools of thought on the issues under investigation. Results: The study showed the permissibility of a non-Muslim having custody of a Muslim and the residing with them, provided there is no harm to the ward. In all circumstances, the father is responsible for financial support of the child as long as he is alive. Conclusion: The research has important findings: the flexibility of Islamic jurisprudence in dealing with various issues, despite different times, places and conditions, the accuracy of the criteria on which custody of young children is established or not, and that the one who takes custody of the child should be the closest and most compassionate person, even if they are non-Muslim, provided that the child is safe with them. The father is responsible for child’s financial support, even if their religions differ. The study recommended expanding practical application of these findings.